2023
DOI: 10.1177/23197145221146348
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Factors Influencing Female Entrepreneurship Intentions and Behaviour

Abstract: There has been an increasing level of interest in female entrepreneurship across the world in recent times. Female entrepreneurship represents a significant aspect of economic growth, particularly in developing countries, leading to job opportunities, socio-economic growth, prospects of innovation, poverty reduction, etc. Nevertheless, despite the growing awareness of its prominence, the research in this area has received limited attention in the entrepreneurship literature. While traditional cultural norms ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Efforts should also be made to promote cultural values that support women's leadership, such as collaboration and respect for elders. Family upbringing and cultural values have been identified as critical factors that shape Emirati women's leadership aspirations and behaviors (Alomar, 2023). Education and societal expectations have also been recognized as important factors that influence women's leadership development (Al Khayyal et al, 2021;Bullough et al, 2022;Howson, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efforts should also be made to promote cultural values that support women's leadership, such as collaboration and respect for elders. Family upbringing and cultural values have been identified as critical factors that shape Emirati women's leadership aspirations and behaviors (Alomar, 2023). Education and societal expectations have also been recognized as important factors that influence women's leadership development (Al Khayyal et al, 2021;Bullough et al, 2022;Howson, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Welter (2011) suggested that contextual factors help shape individual behavior toward the more extensive entrepreneurial process, whereby entrepreneurial orientation may positively be linked to firm performance (Joshi et al , 2015). However, in reality, women seem less likely to consider entrepreneurship because of perceptual barriers in terms of skills, attitude, resource availability, knowledge and institutional and societal factors (Alomar, 2023; Kariv, 2013). Babcock et al (2003) suggested that women entrepreneurs exhibit less propensity with respect to entrepreneurship than their men counterparts, as they make different choices because of different experiences and the socialization process.…”
Section: Theoretical Framework Literature Review and Hypothesesmentioning
confidence: 99%
“…The literature on women's entrepreneurship focuses on the individual characteristics of women entrepreneurs and their businesses, what might motivate them to set up a business, and business strategies related to financing and networking (Oukaci et al, 2019;Bensoula et al, 2021;Avnimelech, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Tunisia, 23.6% of businesses are run by women, while only 11% own their own businesses 1 A number of reforms aimed at economic restructuring have been undertaken by the public authorities in Tunisia, focusing on developing the private . Women also represent more than 51% of the population (Alomar, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation